PENERAPAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN IPA TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KREATIF DAN HASIL BELAJAR PESERTA DIDIK KELAS VII HANG TUAH SMP NEGERI 1 PEKANBARU TAHUN AJARAN 2015/2016 - Wahyuni, Sri; L, Mariani Natalina; Febrita, Elya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :This research aimed to improve creative thinking skill and student’s achievement of student class VII Hang Tuah SMP Negeri 1 Pekanbaru by implementation Problem Based Learning model. It had been done in SMP Negeri 1 Pekanbaru on April-May 2016. Parameters measure were student’s creative thinking skill, studen’t achievement and student’s attitude. The methods of this research was classroom action research by implementation Problem Based Learning model. It had been done in two cylce. There were planning step, acting step, observation step and reflection step for each cycle. The research instrument used was a learning device that consist of a lesson plan, syllabus, assesment authentic sheet, observation sheet and creative thinking skill sheet. The collected data was analysed descriptively. The result of this research showed that creative thinking skill on first cycle was 86,89 (C) and increased on second cycle up to 96,19 (A). Student’achievement on first cycle was 90,62 (B) and increased on second cycle up to 96,48 (A). Classical completeness percentage on both of cycle was 100%. Student’s attitude on first cycle was 87,45 (C) and increased on second cycle up to 93,14 (B). It can be conclude that Problem Based Learning model can improve creative thingking skill and student’s achievement of student class VII Hang Tuah SMP Negeri 1 Pekanbaru.Key Words : Problem Based Learning, Creative Thinking Ability, Student’s Achievement